(untitled) (Research, Society and Development, 2025)
This study aims to systematically analyze the available evidence in the literature regarding the efficacy, safety, and clinical applicability of dexmedetomidine in pediatric patients, considering its main pharmacological, hemodynamic, and neuroprotective outcomes, with emphasis on differences between administration routes and the practical implications for modern anesthesiology. Dexmedetomidine (DEX) is a highly selective alpha-2 adrenergic agonist that has gained prominence in pediatric sedation due to its sedative, analgesic, and anxiolytic properties, with minimal respiratory depression and a stable hemodynamic profile. An integrative literature review was conducted in the PubMed, SciELO, and LILACS databases, using descriptors in Portuguese, English, and Spanish, to evaluate the available evidence on the efficacy, safety, and clinical applicability of DEX in pediatric patients. Full-text articles published between 2021 and 2025 addressing the use of DEX for pediatric sedation were included, resulting in 20 selected studies out of an initial 177. The results indicate that DEX significantly reduces agitation and postoperative delirium and presents cardioprotective and neuroprotective effects. The intranasal route proved safe and well tolerated, with a low incidence of adverse events, while the intravenous route requires caution due to the possibility of transient bradycardia and hypotension. It is concluded that dexmedetomidine represents a promising and safe option for sedation and analgesia in pediatrics, with the potential to reduce opioid use and recovery time, although further multicenter long-term studies are needed to standardize dosing and infusion protocols and consolidate its routine use.